Experimental characterization of the effect of E × B shear on edge-harmonic oscillation mode structure. (13th June 2019) - Chen, M; Luo, C; Zhu, Y; Luhmann, N C; Tobias, B J; Diallo, A; Kramer, G J; Ren, Y; Burrell, K; Mckee, G R; Yan, Z
Abstract: The edge-harmonic oscillation (EHO) mode is one of the characteristic modes that provides an edge transport channel during high-confinement ELM-free phase (the so-called Quiescent High-confinement phase). Recent theoretical work and extensive experimental observations have suggested that the large rotational E  ×  B shear is the key to destabilize an EHO. As the eigenmode grows to large amplitude, it will exert a drag on the rotation, resulting in EHO's saturation (Snyder et al 2007 Nucl. Fusion 47 961). However, detailed mechanisms concerning this process remain vague. We have performed continuous tracking on how the E  ×  B shear affects the EHO mode structure to search for a possible explanation of the saturation mechanism. Two edge density fluctuation diagnostics are employed to observe the eigenmode structure evolution of EHO in the pedestal region in the radial and poloidal directions, respectively. Our results show that the EHO mode's radial wavenumber is strongly correlated with the E  ×  B shear rate, while the poloidal wavenumber is unaffected by the E  ×  B shear rate. During the EHO existence, with the E  ×  B shearing rate ramping down, the radial wavenumber is also observed to be decreasing.